2005
DOI: 10.1021/jf051005o
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Copigments and Grape Cultivar on the Color of Red Wines Fermented after the Addition of Copigments

Abstract: The prefermentation addition of copigments led to significantly different red wines according to the copigment structure (flavonol or hydroxycinnamic acid) and the grape cultivar [Tempranillo (= Cencibel) or Cabernet Sauvignon]. The flavonol rutin enhanced copigmentation and anthocyanin extraction, improving the red color, but the hydroxycinnamic acids (especially caffeic acid) had converse results. The above effects were higher in Cabernet Sauvignon wines, particularly if rutin or p-coumaric acid was used. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
105
0
26

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(141 citation statements)
references
References 38 publications
10
105
0
26
Order By: Relevance
“…Dur study showed that MT-1 and MT-2 treatment promoted the accumulation of some particular anthocyanins in grapes but decreased the total amount of anthocyanins in grapes and MT-2-treated wine. Taking into account the fact that anthocyanins and flavonols share most of their biosythetic pathway, with anthocyanin metabolism preferentially activated compared to flavonol's, thus it should be recognized that flavonols are important copigments that contribute to 4wine colour stability (Schwarz et al, 2005). The higher level of flavonols result from the application of melatonin showed in Table 4 may make up for the deficiency of anthocyanin's lower one to some extent.…”
Section: Effect Of Melatonin Treatment On Individual Anthocyanin Phenmentioning
confidence: 99%
“…Dur study showed that MT-1 and MT-2 treatment promoted the accumulation of some particular anthocyanins in grapes but decreased the total amount of anthocyanins in grapes and MT-2-treated wine. Taking into account the fact that anthocyanins and flavonols share most of their biosythetic pathway, with anthocyanin metabolism preferentially activated compared to flavonol's, thus it should be recognized that flavonols are important copigments that contribute to 4wine colour stability (Schwarz et al, 2005). The higher level of flavonols result from the application of melatonin showed in Table 4 may make up for the deficiency of anthocyanin's lower one to some extent.…”
Section: Effect Of Melatonin Treatment On Individual Anthocyanin Phenmentioning
confidence: 99%
“…From the view of the same branch, cyanidin-type anthocyanins together with quercetin-type and myricetin-type flavonols are dramatically more enhanced by high-altitude cultivation than other types of compounds in a high-altitude region like Shuori. Flavonols are a group of important co-pigment molecules that could stabilise colour to some extent during winemaking (Schwarz et al, 2005). It can be concluded that high altitude conditions promote the quality of the grape berry as related to colour and co-pigmentation in wine.…”
Section: Figurementioning
confidence: 99%
“…From a food chemistry perspective, flavonol glycosides define the color of wine grapes and products by acting as copigments (Yoshitama et al, 1992;Boulton, 2001;Schwarz et al, 2005). Thus, they are important phytochemicals for viticulture and enology.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonol aglycons are biosynthesized from dihydroflavonols by the action of flavonol synthase (Vv FLS), a 2-oxoglutarate-dependent dioxygenase, which is temporally regulated by an R2R3-Myb transcription factor, Vv MYBF1 (Fujita et al, 2006;Czemmel et al, 2009). Subsequently, glycosylation of flavonols enhances their water solubility, such that high concentrations of flavonols can accumulate in plant cells.From a food chemistry perspective, flavonol glycosides define the color of wine grapes and products by acting as copigments (Yoshitama et al, 1992;Boulton, 2001;Schwarz et al, 2005). Thus, they are important phytochemicals for viticulture and enology.…”
mentioning
confidence: 99%